MENANAMKAN NILAI-NILAI KEPEDULIAN SOSIAL PADA SISWA SD TERHADAP IMPLEMENTASI MATA PELAJARAN IPS - Arita Marini; Sebastian, Yosua; Dewi Larasati; Nabila Putri Herdianti; Rufi Nurfaima; Syifa Sabrina (Bajang Institute, 2023)
The flow of globalization also has a negative impact on social life, namely the erosion of social character values in students. Ironically, in this modern era, the world of education, especially in Indonesia, is from time to time faced with various problems, one of which is education which is actually a means of making the nation's life smarter. The school seeks to form a socially caring character through classroom learning, including social studies learning. Good behavior or attitudes towards other people are called social care characters, an example of which is infaq activities. The aim of this research is to determine efforts to instill social care values in elementary school students through learning social studies subjects. This study refers to the library research method (library search) which uses literature to facilitate analysis of research results. Through writing this study, it is hoped that elementary school students can develop social care personalities through social studies learning so that these students can become better individuals.